Description of Premarital Health Status In Pregnancy Preparation - Silvia Ari Agustina; Liberty Barokah; Dewi Zolekhah (Midwifery and Nursing Research, 2022)
Backgrounds: The prospective bride are the right target in improving reproductive health, especially before pregnancy. Prospective brides need to prepare for reproductive health so that after marriage they are expected to have optimal health status. The period before pregnancy, giving birth to the first 1000 days of a baby's life is a golden period that needs attention. Good health status will produce quality generations and reduce mortality and morbidity rates. The purpose of this study was to describe the health status of the prospective bride in preparation for pregnancy. Methods: The research type is descriptive quantitative. The sampling technique used was purposive sampling. The sample in this study amounted to 155 respondents, is secondary data from the health center in 2020. The data analysis uses univariate analysis. Results: Description of the prospective brides health status are, 81.9% were aged 20-35 years, had no history of disease 100%, had normal blood pressure 85.2%, BMI was not normal 52.3%, hemoglobin levels were normal 96.8%, blood sugar was normal 98.06%, normal upper arm circumference 85.8%. Conclusion: The majority of the health status of the bride-to-be is normal and the health status that requires the most attention is less BMI and more.